Baby animals - Geatches, Hazel; Pitts, Sorrel (UK Ladybird Books, 2017)
Some baby animals are small, and some baby animals are big. All baby animals love to play and learn!
Inspired by BBC Earth TV series and developed with input from BBC Earth natural history specialists
Science (Animals)
Keywords: Animals